Early diagnosis and prevention of pelvic and urodynamic dysfunctions in women after delivery - Anna A. Mikhelson; Galina B. Malgina; Ksenia D. Lukianova; Mariia V. Lazukina; Evgenia V. Lugovykh; Anatoly N. Varaksin; Maria A. Lukach; Elvira A. Nesterova (IP Berlin A.V., 2022)
Background. According to various researchers, obstetric perineal injury is the most commOn complication in childbirth, the frequency of which can vary from 13 to 85%. Currently, vaginal delivery and birth trauma are recognized as the leading risk factors for the development of pelvic, urodynamic and sexual dysfunctions. Urinary and fecal incontinence, pelvic organ prolapse, sexual health disorders, chronic pelvic pain and the presence of cosmetic defects in the perineum are the reasons for a significant decrease in the quality of life of women after delivery. Recently, there has been a tendency to "rejuvenate" dysfunctions of the ligamentous apparatus and muscles of the pelvic floor, which support the pelvic organs in a normal position in women after the first birth. In the absence of timely diagnosis and treatment, anatomical changes and clinical symptoms will rapidly progress, forming persistent dysfunctions of the pelvic organs. Aim. To evaluate pelvic and urodynamic dysfunctions in women after per vias naturales delivery with concomitant perineal trauma. Materials and methods. A prospective cohort comparative study was conducted, which included 55 women of reproductive age after delivery per vias naturales of the fetus in cephalic presentation. The main group consisted of 30 women who had a perineal injury during childbirth, the control group included 25 women with uncomplicated straining period. All patients 34 months after delivery underwent a gynecological examination with perineometry, ultrasound examination of the pelvic organs, as well as a comprehensive urodynamic study. Results. Women with a perineal injury during childbirth were significantly more likely to complain of frequent urination and urinary incontinence during physical exertion than women in the control group 70.0% versus 40.0% and 76.7% versus 40.0% of cases respectively (p0.05). According to the ultrasound data, the patients of the main group had a significantly more pronounced deviation of the angle and the angle during straining in comparison with the control group 4.672.6 versus 2.651.1 and 11.937.1 versus 7.104.7 respectively (p0.05). Statistically significant differences were also obtained when measuring the strength of the pelvic floor muscles in patients with perineal injury in comparison with the control group 68.175.8 mmHg versus 76.805.3 mmHg (p0.05). According to urofluometry, the patients of the main group showed a statistically significant decrease in the rate of average and maximum urine flow than in the women of the control group 11.693.8 ml/sec versus 17.902.1 ml/sec and 20.617.0 ml/s versus 25.223.1 ml/s respectively (p0.05). Conclusion. The results obtained indicate the occurrence of urodynamic and pelvic disorders in women during the first 4 months after childbirth, complicated by perineal trauma. In women who have experienced birth trauma, such pelvic and urodynamic dysfunctions as hypermobility of the urethrovesical segment in 86% of cases, a decrease in the strength of the pelvic floor muscles in 54% of cases, and a decrease in the average urine flow rate in 25% of cases were revealed. These disorders can be diagnosed using available non-invasive instrumental examination methods, such as ultrasound, perineometry and uroflowmetry. Thus, there is a need for early detection of pelvic floor dysfunctions for the purpose of subsequent treatment after childbirth, which in turn will help prevent the progression of genital prolapse and urinary incontinence, prevent their severe forms, reduce the need for surgical interventions and preserve the quality of life of women.